The influence of religious coping on the mental health of disabled Iranian war veterans - Aflakseir, Abdulaziz (Mental health, religion & culture, 2009)
This study examined the contribution of religious coping alongside physical function, personal meaning, and social support on the mental health of Iranian veterans. In particular, it was hypothesized that religiosity in a Muslim sample would show associations with well-being independently of other psychological and social variables. A sample of disabled war veterans of the Iran-Iraq was studied (N = 78). Results showed that when physical function, social support, and personal meaning were controlled, religious coping had a significant contribution on mental health indicators including general mental health and PTSD above and beyond other predictors. Of the other predictors investigated only social support make an independent significant contribution to the mental health of veterans. Furthermore, the results demonstrated that participants used positive religious coping strategies more frequently than negative religious coping strategies in coping with their physical disability problems and traumatic experiences